2010
DOI: 10.3109/02770901003759436
|View full text |Cite
|
Sign up to set email alerts
|

Variability in Childhood Asthma and Body Mass Index Across Northern Plains American Indian Communities

Abstract: The intertribal differences in asthma prevalence noted here emphasize the need for further understanding the intertribal environmental, social, and behavioral factors that are associated with childhood asthma and obesity. Such knowledge can help inform disease prevention or disease management strategies that encompass the unique characteristics of tribal communities and culture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 28 publications
3
21
0
Order By: Relevance
“…In this report, Noonan et al . observed that overweight and obese youth were 1.72 times as likely to have current asthma compared to those of normal weight (28), an estimate nearly identical to those we reported in our study for overweight and obese youth, respectively.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In this report, Noonan et al . observed that overweight and obese youth were 1.72 times as likely to have current asthma compared to those of normal weight (28), an estimate nearly identical to those we reported in our study for overweight and obese youth, respectively.…”
Section: Discussionsupporting
confidence: 89%
“…Specifically, these investigators found that youth with asthma were 1.34 times as likely to be overweight, and 1.51 times as likely to be obese (12); these estimates of association are relatively similar to those we report in our study. Despite our modest American Indian/ Native Alaskan sample size (n = 610), which limited our power to detect associations in some BMI groups, our findings of increased asthma prevalence among obese American Indian/ Alaskan Native youth are highly consistent with a recent study conducted in 1,852 children from Northern Plains American Indian communities (28). In this report, Noonan et al observed that overweight and obese youth were 1.72 times as likely to have current asthma compared to those of normal weight (28), an estimate nearly identical to those we reported in our study for overweight and obese youth, respectively.…”
Section: Discussionsupporting
confidence: 86%
“…Previously gathered data demonstrated a two- to four-fold increase in obesity rates among American–Indian children in the Northern Plains region of the USA when compared with the national average [39]. Obesity and being overweight are major risk factors for T2D.…”
Section: Cbpr In Diabetes and Obesitymentioning
confidence: 99%
“…However, little is known about the prevalence of asthma among Alaska Native children, as they have historically been underrepresented in the paediatric asthma literature. Existing studies describing asthma among AI/AN children have largely relied on the review of existing medical records or the use of aggregated data, with the reported results highly variable (2226). …”
mentioning
confidence: 99%